The black swan problem : risk management strategies for a world of wild uncertainty - Jankensgård, Håkan (John Wiley & Sons, Inc., 2022)
"Proactive risk management is a common buzzword nowadays and a hot topic in the corporate world. The execution, however, is not as easy as it may seem. We essentially live in a world of "wild uncertainty" instead of neat probabilities. What should managers do about it? The book explores different basic approaches -- high-level strategies -- for navigating in such a world. It argues that getting organizational culture and analytics right is a key aspect of making firms less "swan-prone." It explains and maps out the three generic strategies for increasing resilience/antifragility: insurance, buffers and flexibility. Intriguingly, however, resilience and antifragility may not be the primary goals of some firms. There may in fact be a case to be made for engaging in "big-wave surfing" and maximising exposure to the swans. The book also covers some fascinating theories about risk-taking in firms, showing that the BSP is about more than just minimising risk. The book will: Explain in detail, and using examples and stories (e.g. Norwegian, Netflix, Texas energy retailer Griddy, private equity sector, BP, etc.), how the commonly misunderstood Swans function, and the mechanisms that bring them about. Extend the typical focus on individual biases to analyse Swans as an organizational problem Elevate the Swans to the level of strategy and explains how Swans are make-it-or-break-it moments for firms Discuss important differences between different kinds of Swans Illustrate various practical applications and tactics related to the generic strategies of insurance, buffers and flexibility"--